Personality Trait Changes After Device-Aided Therapy : Insights From Parkinson’s Patients and Their Close Relatives - Scharfenort, Monica; Hernström, Veronica ; 0009-0007-6597-3654; Rosqvist, Kristina; Ljung, Hanna; Nilsson, Maria H. ; 0000-0002-6580-6721; Odin, Per ; 0000-0002-0756-7478 (Parkinson's Disease, 2025)
Background: It is unclear whether the two device-aided therapies (DATs: deep brain stimulation [DBS] and levodopa–carbidopa intestinal gel [LCIG]) affect personality in patients with Parkinson’s disease (PD). Objective: This retrospective study aims to explore if patients with PD and their close relatives experience any changes in the patient’s personality following the start of DAT. Methods: In total, 32 patients with DAT (17 DBS and 15 levodopa pump–based therapy) and their close relatives (n = 32) were asked to retrospectively assess potential personality changes in the patients using the Big Five Inventory (BFI) following DAT. They also answered questions regarding perceived quality of life and perceived impact on motor symptoms. Results: There was a diverse perceived change in the patients’ five personality traits when divided into the type of therapy. DBS patients reported decreased extraversion (70.6%, n = 12), while their close relatives reported an increase in the trait neuroticism (82.4%, n = 14). A significant difference was found in perceived changes in agreeableness, with 8 DBS patients reporting an increase and 4 close relatives reporting a decrease (p = 0.008). Most of the pump patients (LCIG) reported a decreased conscientiousness (66.7% n = 10), a perception confirmed by 73.3% (n = 11) of their close relatives, who in addition reported an increase in neuroticism (73.3%, n = 11). Conclusions: This study suggests perceived personality changes following DAT (DBS or LCIG), which vary by therapy and respondent role. Larger studies are needed, but the findings signal the importance of considering both patients’ and their relatives’ perspectives when assessing personality changes.
Publisher Copyright: Copyright © 2025 Monica Scharfenort et al. Parkinson’s Disease published by John Wiley & Sons Ltd.
Keywords: carbidopa–levodopa drug combination; deep brain stimulation; infusion pumps; Parkinson’s disease; personality; personality assessment; the Big Five Inventory